SOCIOCULTURAL ENVIRONMENT AS A FACTOR AND RESOURCE MANAGEMENT (Journal of Philosophy Culture and Political Science, 2018)
Changing of professional, communicative, political, consumer culture plays the key role in the process of global Social cultural space forming and generates new risk factors in the area of local cultures confrontation. But on the other hand it opens some new perspectives for to understand the principles of social regulation resources forming. Environmental factors represent an actual problem of anthropogenic society dynamics, and this fact stimulates research of social cultural environment as management significant factor and resource.